The Impact of Implicit vs. Explicit Grammar Teaching through Scaffolding on Iranian Learners’ Speaking Motivation and Self-Efficacy: ESP Students in Focus - Aliakbar Moeen; Daryoush Nejadansari; Azizolla Dabaghi (Iranian Evolutionary Educational Psychology Journal, 2023)
The present study was conducted to investigate the role of implicit vs explicit grammar teaching through teacher scaffolding in the improvement of speaking motivation and self-efficacy among Iranian pre-intermediate EFL learners. To this end, In line with the objectives of the present study, a quasi-experimental pre-test post-test control group design was used. 90 ESP students of architecture and art studying in Azad University of Yazd participated in this study through available sampling. These participants were divided into three groups (explicit, implicit, and control groups). The research instruments employed to collect data for this study were Oxford Placement Test, Hogan and Pressely’s (1997) Guidelines for Teacher Scaffolding, Gardner’s Attitude/Motivation Test Battery, and General Self-efficacy Scale. The obtained data were analyzed through one-way analysis of variance (ANOVA) using SPSS software. The obtained results indicated that using scaffolding techniques accompanied by explicit/implicit grammar instruction had a significant effect on self-efficacy and motivation of Iranian pre-intermediate EFL learners. Moreover, it was indicated that that using scaffolding techniques accompanied by explicit grammar instruction and implicit grammar instruction were equally effective on self-efficacy and motivation of Iranian pre-intermediate EFL learners. This confirmed that scaffolding techniques have significantly affected self-efficacy and motivation of learners. This study has some implications for teachers and students involved in EFL context.